Pregunta
upstudy study bank question image url

Solve for \( x \) and \( y \) simultanously (1) \( 3 x+2 y=7 \) and \( -3 x+y=1 \) (2) \( x+3 y=17 \) and \( 4 x-2 y=12 \) (3) \( x+2 y=13 \) and \( 3 x-y=4 \)

Ask by Joseph Carrillo. in South Africa
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are: 1. \( x = \frac{5}{9} \), \( y = \frac{8}{3} \) 2. \( x = 5 \), \( y = 4 \) 3. \( x = 3 \), \( y = 5 \)

Solución

Solve the system of equations \( 3x+2y=7;-3x+y=1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+2y=7\\-3x+y=1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}3x+2y=7\\y=1+3x\end{array}\right.\) - step2: Substitute the value of \(y:\) \(3x+2\left(1+3x\right)=7\) - step3: Simplify: \(9x+2=7\) - step4: Move the constant to the right side: \(9x=7-2\) - step5: Subtract the numbers: \(9x=5\) - step6: Divide both sides: \(\frac{9x}{9}=\frac{5}{9}\) - step7: Divide the numbers: \(x=\frac{5}{9}\) - step8: Substitute the value of \(x:\) \(y=1+3\times \frac{5}{9}\) - step9: Calculate: \(y=\frac{8}{3}\) - step10: Calculate: \(\left\{ \begin{array}{l}x=\frac{5}{9}\\y=\frac{8}{3}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=\frac{5}{9}\\y=\frac{8}{3}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(\frac{5}{9},\frac{8}{3}\right)\) Solve the system of equations \( x+3y=17;4x-2y=12 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+3y=17\\4x-2y=12\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=17-3y\\4x-2y=12\end{array}\right.\) - step2: Substitute the value of \(x:\) \(4\left(17-3y\right)-2y=12\) - step3: Simplify: \(68-14y=12\) - step4: Move the constant to the right side: \(-14y=12-68\) - step5: Subtract the numbers: \(-14y=-56\) - step6: Change the signs: \(14y=56\) - step7: Divide both sides: \(\frac{14y}{14}=\frac{56}{14}\) - step8: Divide the numbers: \(y=4\) - step9: Substitute the value of \(y:\) \(x=17-3\times 4\) - step10: Calculate: \(x=5\) - step11: Calculate: \(\left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=5\\y=4\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(5,4\right)\) Solve the system of equations \( x+2y=13;3x-y=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+2y=13\\3x-y=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=13-2y\\3x-y=4\end{array}\right.\) - step2: Substitute the value of \(x:\) \(3\left(13-2y\right)-y=4\) - step3: Simplify: \(39-7y=4\) - step4: Move the constant to the right side: \(-7y=4-39\) - step5: Subtract the numbers: \(-7y=-35\) - step6: Change the signs: \(7y=35\) - step7: Divide both sides: \(\frac{7y}{7}=\frac{35}{7}\) - step8: Divide the numbers: \(y=5\) - step9: Substitute the value of \(y:\) \(x=13-2\times 5\) - step10: Calculate: \(x=3\) - step11: Calculate: \(\left\{ \begin{array}{l}x=3\\y=5\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=5\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(3,5\right)\) The solutions to the given systems of equations are: 1. \( x = \frac{5}{9} \) and \( y = \frac{8}{3} \) 2. \( x = 5 \) and \( y = 4 \) 3. \( x = 3 \) and \( y = 5 \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

Alright! Let's dive into solving these simultaneous equations! For the first set of equations: (1) \( 3x + 2y = 7 \) (2) \( -3x + y = 1 \) From equation (2), we can express \( y \): \[ y = 1 + 3x \] Now substitute this into equation (1): \[ 3x + 2(1 + 3x) = 7 \] \[ 3x + 2 + 6x = 7 \] \[ 9x + 2 = 7 \] \[ 9x = 5 \] \[ x = \frac{5}{9} \] Now substitute \( x \) back to find \( y \): \[ y = 1 + 3\left(\frac{5}{9}\right) = 1 + \frac{15}{9} = 1 + \frac{5}{3} = \frac{8}{3} \] So the solution is \( x = \frac{5}{9} \) and \( y = \frac{8}{3} \). --- For the second set of equations: (1) \( x + 3y = 17 \) (2) \( 4x - 2y = 12 \) From equation (1), solve for \( x \): \[ x = 17 - 3y \] Substitute this into equation (2): \[ 4(17 - 3y) - 2y = 12 \] \[ 68 - 12y - 2y = 12 \] \[ 68 - 14y = 12 \] \[ -14y = 12 - 68 \] \[ -14y = -56 \] \[ y = 4 \] Now substitute \( y \) back to find \( x \): \[ x = 17 - 3(4) = 17 - 12 = 5 \] So the solution is \( x = 5 \) and \( y = 4 \). --- For the third set of equations: (1) \( x + 2y = 13 \) (2) \( 3x - y = 4 \) From equation (1), solve for \( x \): \[ x = 13 - 2y \] Substituting this into equation (2): \[ 3(13 - 2y) - y = 4 \] \[ 39 - 6y - y = 4 \] \[ 39 - 7y = 4 \] \[ -7y = 4 - 39 \] \[ -7y = -35 \] \[ y = 5 \] Now substitute \( y \) back to find \( x \): \[ x = 13 - 2(5) = 13 - 10 = 3 \] So the solution is \( x = 3 \) and \( y = 5 \). ### Summary of Solutions: 1. \( x = \frac{5}{9}, y = \frac{8}{3} \) 2. \( x = 5, y = 4 \) 3. \( x = 3, y = 5 \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad